2013
DOI: 10.1111/dme.12289
|View full text |Cite
|
Sign up to set email alerts
|

The use of technology to promote physical activity in Type 2 diabetes management: a systematic review

Abstract: Technology-based interventions to promote physical activity are effective; using further methods to promote participant adherence is associated with greater benefit. Further research should look into strategies to enhance adherence and sustainability in order to increase the effectiveness of technology-based physical activity intervention in diabetes care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
109
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(114 citation statements)
references
References 29 publications
4
109
0
1
Order By: Relevance
“…Although the eHealth interventions we studied uniformly improved PA outcomes, it is interesting to note that only two of the six eHealth interventions that we studied were in the top tertile by PRECIS-2 scores. To improve the pragmatism of future PA interventions using eHealth methods, one opportunity may be to SYSTEMATIC REVIEWS enhance the linkage of PA tracking to existing electronic medical records [83]. This linking would allow clinicians and patients to more readily monitor physical activity levels and communicate regarding new activity goals.…”
Section: Discussionmentioning
confidence: 99%
“…Although the eHealth interventions we studied uniformly improved PA outcomes, it is interesting to note that only two of the six eHealth interventions that we studied were in the top tertile by PRECIS-2 scores. To improve the pragmatism of future PA interventions using eHealth methods, one opportunity may be to SYSTEMATIC REVIEWS enhance the linkage of PA tracking to existing electronic medical records [83]. This linking would allow clinicians and patients to more readily monitor physical activity levels and communicate regarding new activity goals.…”
Section: Discussionmentioning
confidence: 99%
“…For example, technology that tracks behavior over time and allows the user to see their own behavior trends in a visual format have been found to positively impact health behavior (18). Not surprisingly, apps that lack the ability to engage users lessen the impact of the app effectiveness on behavior change (1).…”
Section: Introductionmentioning
confidence: 99%
“…Not surprisingly, apps that lack the ability to engage users lessen the impact of the app effectiveness on behavior change (1). Lastly, online advice from a personal coach was more influential on user behavior than peer support (18). It has also been suggested that apps utilize expertise from health professionals for monitoring and feedback as well as provide the user with a more personalized experience to increase adherence to health behaviors (13).…”
Section: Introductionmentioning
confidence: 99%
“…Technological tools, such as eHealth (electronic health) and mHealth (mobile health) applications, will be increasingly integrated in supporting self-management. [4] For example, Azevedo, et al [5] are convinced that mobile health applications will be useful in regulating self-management in long-term illnesses. Furthermore, eHealth solutions can particularly help patients to improve access to health care in sparsely populated countries such as Finland.…”
Section: Background Of the Studymentioning
confidence: 99%